Producción y caracterización de multicapas de alta dureza basadas en nitruro de titanio por técnica DC Magnetrón Sputtering - Asencios Rojas, Junior David (2016)
In this thesis we explore the possibilities to obtain hardness enhancement in three different types of multilayer system: TiN/AlN, TiN/NbN and TiN/TaN, produced by bias-dc magnetron sputtering under the same deposition conditions. Multilayer structure and chemical composition were confirmed by GDOES (Glow discharge optical emission spectroscopy). Complementary chemical analyses were also carried out by AES and EDS. Crystalline structure of component layers was studied by XRD (X-ray diffraction). Microhardness was measured by using a classic Vickers microdurometer and SEM (Scanning electron microscopy), as well as, by nanoindentation. Corrosion current was determined by Tafel extrapolation metho